Exploration of bioactive compounds in invasive plant Spathodea campanulata flower originating from Bukit Barisan National Park, Lampung, Indonesia - DURYAT DURYAT; RAFLI INDRA GHOZALI; YOPPIE JORDAN SARAGIH; RODIANI RODIANI; TRI MARYONO; CITRA YULIYANDA PARDILAWATI; ISMANTO ISMANTO (Society for Indonesian Biodiversity, 2025)
Abstract. Duryat, Ghozali RI, Saragih YJ, Rodiani, Maryono T, Pardilawati CY, Ismanto. 2025. Exploration of bioactive compounds in invasive plant Spathodea campanulata flower originating from Bukit Barisan National Park, Lampung, Indonesia. Biodiversitas 26: 366-376. The African tulip tree (Spathodea campanulata), an invasive alien species, poses a significant ecological threat but offers promising bioactive compounds with therapeutic potential. This study aimed to profile the bioactive compounds present in the flowers of S. campanulata sourced from the Utilization Zone of Pemerihan Resort, Bukit Barisan Selatan National Park (BBSNP), Lampung, Indonesia. Using ethanol extraction followed by LC-MS and GC-MS analysis, 11 bioactive compounds were identified, comprising six volatile and five non-volatile compounds. These compounds, categorized into flavonoids, alkaloids, amino acids, and iridoids, exhibited 13 notable medical properties, including anti-inflammatory, anticancer, antimicrobial, antioxidant, and anticholinergic activities. The findings highlight the potential of S. campanulata flowers in addressing some of the world's deadliest diseases, such as cancer, chronic obstructive pulmonary disease (COPD), respiratory infections, and coronary artery disease. Despite these promising results, further research is essential to translate these findings into practical applications. Future studies should focus on in vitro and in vivo pharmacological evaluations, toxicity assessments, clinical trials, and compound synthesis and dosing optimization. The discovery of these bioactive compounds underscores the dual role of invasive species as both ecological challenges and valuable resources for pharmaceutical development.